Human province - "Canetti, Elias" (London, 1985)
This book is a record of thirty years in an intensely conscious existence. It records the evolution of Elias Canetti's life and thought in both their spiritual and intellectual contexts, thus becoming a collection a personal revelations rather than merely of diary entries or aphorisms.
Keywords: "Canetti, Elias -Biography."